2022
DOI: 10.1038/s41569-022-00679-9
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue in contemporary cardiology

Abstract: Interest in epicardial adipose tissue (EAT) is growing rapidly, and research in this area appeals to a broad, multidisciplinary audience. EAT is unique in its anatomy and unobstructed proximity to the heart and has a transcriptome and secretome very different from that of other fat depots. EAT has physiological and pathological properties that vary depending on its location. It can be highly protective for the adjacent myocardium through dynamic brown fat-like thermogenic function and harmful via paracrine or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
227
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(322 citation statements)
references
References 160 publications
(218 reference statements)
6
227
0
10
Order By: Relevance
“…Epicardial adipose tissue (EAT) is a visceral fat with a peculiar anatomical contiguity with the myocardium. A positive correlation between EAT thickness and cardiac diseases has been shown [5,6].…”
Section: Introductionmentioning
confidence: 95%
“…Epicardial adipose tissue (EAT) is a visceral fat with a peculiar anatomical contiguity with the myocardium. A positive correlation between EAT thickness and cardiac diseases has been shown [5,6].…”
Section: Introductionmentioning
confidence: 95%
“…Ischemic heart disease and endomyocardial fibrosis are the primary causes of heart failure, and it is well established that perivascular and epicardiac AT participates in cardiac cell alteration during metabolic diseases through the release of proinflammatory cytokines [30]. In the context of atrial fibrillation, it has been found that epicardiac adipose tissue also exports EVs (epAT-EVs) with profibrotic and proarrhythmic properties [31].…”
Section: Epicardiac Adipocyte-derived Evsmentioning
confidence: 99%
“…In this paper, we review papers that segment whole EAT or PAT volumes from their surrounding tissues, and not papers that aim to segment different regions inside EAT or PAT, such as left atrial EAT vs. left ventricular EAT. While there is evidence that the distribution of EAT around the heart is important [5], segmenting the whole volume is a prerequisite for the analysis of its distribution and is, therefore, the focus of this review.…”
Section: Introductionmentioning
confidence: 99%